2006
DOI: 10.1111/j.1462-5822.2006.00859.x
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic lipopolysaccharides blockE. colilipopolysaccharide function at human TLR4 via interaction with the human MD-2 lipopolysaccharide binding site

Abstract: SummaryLipopolysaccharides containing underacylated lipid A structures exhibit reduced abilities to activate the human (h) Toll-like receptor 4 (TLR4) signalling pathway and function as potent antagonists against lipopolysaccharides bearing canonical lipid A structures. Expression of underacylated lipopolysaccharides has emerged as a novel mechanism utilized by microbial pathogens to modulate host innate immune responses. Notably, antagonistic lipopolysaccharides are prime therapeutic candidates for combating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 64 publications
2
49
0
1
Order By: Relevance
“…Tissue invasion by strict anaerobes may be limited most effectively by high oxygen tension (redox potential), although some of these bacteria may be able to induce inflammatory defenses via TLR2 (25). It is noteworthy that, at least in vitro, Bacteroides and Porphyromonas LPS can block the ability of hexaacyl LPS to stimulate cells via MD-2-TLR4 (20,29). Whether this competition between hexaacyl and nonhexacyl LPS can modulate TLR4-based sensing in the (sub)mucosae of the respiratory tract or intestine is not known.…”
Section: Host Recognition Of Lps and The Pathogenesis Of Gram-negativmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue invasion by strict anaerobes may be limited most effectively by high oxygen tension (redox potential), although some of these bacteria may be able to induce inflammatory defenses via TLR2 (25). It is noteworthy that, at least in vitro, Bacteroides and Porphyromonas LPS can block the ability of hexaacyl LPS to stimulate cells via MD-2-TLR4 (20,29). Whether this competition between hexaacyl and nonhexacyl LPS can modulate TLR4-based sensing in the (sub)mucosae of the respiratory tract or intestine is not known.…”
Section: Host Recognition Of Lps and The Pathogenesis Of Gram-negativmentioning
confidence: 99%
“…It is also possible that the associations sought so far have not included mucosal infectious diseases, such as shigellosis, in which LPS recognition by MD-2-TLR4 seems to play an important role. Since LPS binds MD-2 (20,45,94), disease-linked polymorphisms in MD-2 also deserve more attention (48). Polymorphisms in other host sensors are more likely to be associated with increased susceptibility to microbes, such as Legionella pneumophila (52) and Y. pestis, that make nonhexaacyl LPS.…”
Section: Limitations Possible Implicationsmentioning
confidence: 99%
“…For example, early studies conducted in our laboratory indicated that not only did P. gingivalis LPS fail to elicit strong host innate immune responses such as E-selectin induction, but it also antagonized the immunostimulatory activity of agonsitic LPS (Darveau et al, 1995). Subsequent investigations demonstrated that the antagonistic capacity displayed by P. gingivalis LPS isolates was due to competitive inhibition of agonistic LPS interaction at the host Toll-like receptor 4 (TLR4) complex (Hajishengallis et al, 2002;Coats et al, 2003;Coats et al, 2005;Coats et al, 2007), which forms a major host sensing mechanism to Gram-negative bacterial infections (Beutler, 2000;Munford et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Type I is a TLR4 agonist, thus activating the immune system, while type II is a TLR4 antagonist inhibiting the immune response to P. gingivalis [57]. The expression of these two types of LPS is regulated by the concentration of iron from the hemin found in the GCF [58]. During inflammatory process, P. gingivalis type II LPS expression increases which reduces the TLR4 response.…”
Section: Host Defense Mechanismsmentioning
confidence: 99%